2021
DOI: 10.1002/pld3.344
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex genome editing in Arabidopsis thaliana using Mb3Cas12a

Abstract: The use of CRISPR-Cas proteins for the creation of multiplex genome engineering represents an important avenue for crop improvement, and further improvements for creation of knock-in plant lines via CRISPR-based technologies may enable the high-throughput creation of designer alleles. To circumvent limitations of the commonly used CRISPR-Cas9 system for multiplex genome engineering, we explored the use of Moraxella bovoculi 3 Cas12a (Mb3Cas12a) for multiplex genome editing in Arabidopsis thaliana. We identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Potentially, more important is the ability of Cas12a to process pre-crRNA, which provides for multiplexing, that is, co-expression of several guides on a single transcript for compact delivery, expression under inducible or state-dependent promoters, or for monitoring of gene expression . Indeed, highly efficient, multiplex, simultaneous genome editing of dozens of targets using Cas12a has been repeatedly demonstrated. , Moreover, efficient simultaneous regulation of multiple genes in mammalian cells by multiplexing with inactivated Cas12a has been reported by several groups. Several studies have reported high specificity of Cas12a, with an extremely low off-target rate. Although the natural diversity of Cas12a is far lower than that of Cas9, Cas12a’s from different bacteria were found to be optimal for different applications in different in vitro and in vivo systems.…”
Section: Harnessing Class 2 Crispr Diversity For Applications In Geno...mentioning
confidence: 99%
See 1 more Smart Citation
“…Potentially, more important is the ability of Cas12a to process pre-crRNA, which provides for multiplexing, that is, co-expression of several guides on a single transcript for compact delivery, expression under inducible or state-dependent promoters, or for monitoring of gene expression . Indeed, highly efficient, multiplex, simultaneous genome editing of dozens of targets using Cas12a has been repeatedly demonstrated. , Moreover, efficient simultaneous regulation of multiple genes in mammalian cells by multiplexing with inactivated Cas12a has been reported by several groups. Several studies have reported high specificity of Cas12a, with an extremely low off-target rate. Although the natural diversity of Cas12a is far lower than that of Cas9, Cas12a’s from different bacteria were found to be optimal for different applications in different in vitro and in vivo systems.…”
Section: Harnessing Class 2 Crispr Diversity For Applications In Geno...mentioning
confidence: 99%
“… 106 Indeed, highly efficient, multiplex, simultaneous genome editing of dozens of targets using Cas12a has been repeatedly demonstrated. 104 , 107 110 Moreover, efficient simultaneous regulation of multiple genes in mammalian cells by multiplexing with inactivated Cas12a has been reported by several groups. 111 114 Several studies have reported high specificity of Cas12a, 115 118 with an extremely low off-target rate.…”
Section: Harnessing Class 2 Crispr Diversity For Applications In Geno...mentioning
confidence: 99%
“…In fact, when solely assessed visually, nuclease activity appears to be reduced at room temperature (22 °C-28 °C) (Moreno-Mateos et al, 2017;LeBlanc et al, 2018;Malzahn et al, 2019;Milner et al, 2020;Schindele and Puchta, 2020), with Cas12a being the most negatively impacted. Editing efficiency is reported to improve when transformed plant tissue is incubated at higher temperature for a shorter period of time (Jordan et al, 2021;Kurokawa et al, 2021). In our work, when all edits were considered (i.e., including monoallelic edits detected only after amplicon sequencing), the beneficial effect of elevated temperature only held true for Mb3Cas12a.…”
Section: Discussionmentioning
confidence: 70%
“…In 2020, Hu et al used modified tRNA-crRNA arrays to not only effectively achieve multiple genome editing in rice, but also to successfully edit target loci that were not edited by crRNA arrays, improving the efficiency of gene editing [ 185 ]. In 2021, William et al performed multiple genome editing in Arabidopsis using Moraxella boroculi 3 Cas12a and successfully achieved the expression of a single transcript with as many as 13 crRNAs [ 186 ]. Temperature is also an essential factor in the efficiency of Cas12a editing.…”
Section: Strategies and Methods For Optimizing Crispr/cas9 Gene-editi...mentioning
confidence: 99%